PENERAPAN DATA MINING DENGAN METODE KLASIFIKASI MENGGUNAKAN ALGORITMA C4.5 - iyan sunandar sunandar; Fauji Faisal Nugraha; Christina Juliane (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The problem of settlements is still the main problem faced by some regions. The unorganized settlement area can create a livable, productive and sustainable residential environment. In addition, the non-fulfillment of Minimum Service Standards (SPM) in several residential areas causes the environmental conditions of the settlements to be inadequate and below the minimum service standards such as low quality of drinking water, drainage, waste, garbage and other problems such as overcrowding and irregularities. buildings which further have implications for increasing fire hazards as well as social impacts such as crime rates which tend to increase from time to time. In this study, the authors use the Data Mining classification method, namely the C4.5 Algorithm to classify activities in obtaining activities with a Very Priority, Priority and Not Priority Scale. The sample of data sources was taken from investment data for the KOTAKU Program activities in Kuningan Regency. From the test results obtained for the Accuracy Algorithm C4.5 value is 95.98%. Thus the C4.5 algorithm is the best algorithm and technique for classifying investment activity data in obtaining aid funds sourced from the government.